Komunikasi Pelayanan Digital Koperasi Melalui Instagram Untuk Meningkatkan Kepuasan Anggota - Farida Farida; Putri Kinkin Azizah Hanum (J-Coop : Journal of Co-operative, 2026)
Digital Communication Services Through Instagram to Increase Member Satisfaction: A Case Study of the Kopmart Business Unit of KOPMA UNISBA. The Student Cooperative of Universitas Islam Bandung (KOPMA UNISBA) utilizes Instagram as a digital communication platform to support its services in the Kopmart business unit. However, declining member participation indicates that digital service communication has not yet been optimally implemented. This study aims to analyze members’ perceptions of digital service communication through Instagram and measure the level of member satisfaction. This research employs a descriptive quantitative approach, utilizing a case study method. Data were collected from 69 active members through questionnaires, supported by interviews, observations, and documentation. The quality of digital service communication was measured using the E-Service Quality (ES-QUAL) dimensions, namely efficiency, system availability, fulfillment, and privacy. Member satisfaction was measured based on product and service quality, price, accessibility, prior experience, and institutional image. Data analysis was conducted using descriptive statistics. The results indicate that digital service communication through Instagram is categorized as “fairly good,” with weaknesses mainly found in system availability, particularly response speed and information accessibility. Member satisfaction is also classified as “fairly good,” with low scores in membership pride, cost transparency, and satisfaction with product innovation. These findings indicate that even though Instagram-based digital communication contributes to member satisfaction, improvements in responsiveness, message consistency, transparency, and innovation are still required.